2020
DOI: 10.1093/mnras/staa507
|View full text |Cite
|
Sign up to set email alerts
|

Faint rapid red transients from neutron star–CO white dwarf mergers

Abstract: Mergers of neutron stars (NS) and white dwarfs (WD) may give rise to observable explosive transient events. We use 3D hydrodynamical (SPH) simulations, as well as 2D hydrodynamical-thermonuclear simulations (using the FLASH AMR code) to model the disruption of CO-WDs by NSs, which produce faint transient events. We postprocess the simulations using a large nuclear network and make use of the SuperNu radiation-transfer code to predict the observational signatures and detailed properties of these transients. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 48 publications
6
60
1
Order By: Relevance
“…At 8 kpc, where the ISM mixing requirement of NS-WD merger models can be satisfied, the SN explosion energy would be only ∼ 4.5 × 10 49 erg, which is too low for a typical SN explosion or the 1D NS-WD merger model of Margalit & Metzger (2016). Although the more sophisticated 2D simulations of Zenati et al (2019Zenati et al ( , 2020 obtained similarly low explosion energy of 10 48 -10 49 erg for NS-CO WD mergers, they showed that the He WD cases cannot lead to any thermonuclear explosion or mass ejection. On the contrary, the explosion energy at 20 kpc is consistent with Ca-rich transient SN 2005E and He shell detonation models (Perets et al 2010;Waldman et al 2011).…”
Section: Disadvantages Of Ns+wd Mergermentioning
confidence: 97%
See 1 more Smart Citation
“…At 8 kpc, where the ISM mixing requirement of NS-WD merger models can be satisfied, the SN explosion energy would be only ∼ 4.5 × 10 49 erg, which is too low for a typical SN explosion or the 1D NS-WD merger model of Margalit & Metzger (2016). Although the more sophisticated 2D simulations of Zenati et al (2019Zenati et al ( , 2020 obtained similarly low explosion energy of 10 48 -10 49 erg for NS-CO WD mergers, they showed that the He WD cases cannot lead to any thermonuclear explosion or mass ejection. On the contrary, the explosion energy at 20 kpc is consistent with Ca-rich transient SN 2005E and He shell detonation models (Perets et al 2010;Waldman et al 2011).…”
Section: Disadvantages Of Ns+wd Mergermentioning
confidence: 97%
“…One of its significant characteristics is the Ca-rich ejecta and the mass of the Ca element may reach ∼ 10 −1 M e . A natural explanation for Ca-rich ejecta is the burning of He-rich matter and there are two leading nucleosynthesis models so far: (i) the accreted WD He shell detonation (Waldman et al 2011); and (ii) the merger of a He-rich WD and a NS (Margalit & Metzger 2016;Zenati et al 2020). Both models predict very large Ar/Si and Ca/Si ratios in the ejecta.…”
Section: Peculiar Thermonuclear Sne: Ca-rich Transientsmentioning
confidence: 99%
“…One of its significant characteristics is the Ca-rich ejecta and the mass of the Ca element may reach ∼ 10 −1 M ⊙ . A natural explanation for Ca-rich ejecta is the burning of He-rich matter and there are two leading nucleosynthesis models so far: i) the accreted WD He shell detonation (Waldman et al 2011); ii) the merger of a He-rich WD and a NS (Margalit & Metzger 2016;Zenati et al 2020). Both models predict very large Ar/Si and Ca/Si ratios in the ejecta.…”
Section: Ca-rich Transientsmentioning
confidence: 99%
“…At 8 kpc, where the ISM mixing requirement of NS-WD merger models can be satisfied, the SN explosion energy would be only ∼ 4.5 × 10 49 erg, which is too low for a typical SN explosion or the 1D NS-WD merger model ofMargalit & Metzger (2016). Although the more sophisticated 2D simulations ofZenati et al (2019Zenati et al ( , 2020 obtained similarly low explosion energy of 10 48 -10 49 erg for NS-CO WD mergers, they showed that the He WD cases…”
mentioning
confidence: 99%
“…Thus, bright transients might appear at different wavelengths, including optical range. 2 In [2] the authors studied the outcome of NS-WD mergers in some details from the point of view of electromagnetic counterparts (see also a recent e-print [8]). In particular, they suggested that due to jet formation a high-energy transient can appear.…”
Section: Introductionmentioning
confidence: 99%